Are There Occurrent Continuants? - Riccardo Baratella (Dialectica, 2022)
Processes are occurrents that were, are, or will be happening. They endure or they perdure, i.e. they are either "fully" present at every time they happen, or they rather have temporal parts. According to Stout (2016), they endure. His argument assumes that processes may change. Then, Stout argues that, if something changes, it endures. As I show, Stout's Argument misses its target. In particular, it makes use of a notion of change that is either intuitive but illegitimate or technical but question-begging.